(untitled) (Indian Journal of Public Health Research & Development, 2020)
Objective: To investigate the effect of doxorubicin, cyclophosphamide and taxane chemotherapy on the lipid profile in Iraqi patients with breast cancer. Method: This cohort prospective study was carried out at the Biochemistry Department, Baghdad College of Medical Sciences, and at the Oncology Clinic, Oncology Teaching Hospital, Baghdad, Iraq, during the period from May 2019 to October 2019. It included 56 women with regular menstrual cycle (25-45 years) classified into 3 groups: GI: 29 women with primary breast cancer (before starting chemotherapy), GII: the same 29 women of GI who were finished 4 cycles of anthracycline chemotherapy (course 1) and GIII: which involved another 27 women who had finished both courses of chemotherapy, (course 1) and 4 cycles of taxanes (course 2). Serum cholesterol, LDL, HDL and TG were measured using colorimetric method. Results: The results of the present study showed that the (mean±SEM) of the serum cholesterol was decreased significantly (p<0.05) in GIII compared to GI and highly significantly (p<0.01) compared to GII. While, the serum HDL level was significantly (p<0.05) lower in GIII compared to GI. Concerning the serum LDL level, it was increased significantly (p<0.05) in GII compared to both GI and GIII. While; the serum TG level shows no significant difference between all groups. Conclusion: Iraqi women with breast cancer had an abnormal state of dyslipidemia that become worsened after chemotherapy.